Teacher's Skills in Classroom Management According to the Characteristics of Students in Elementary School - Andhika, M. Rezki; Suroto, Suroto; Syahputra, Rizki; Pasaribu, Laili Habibah (Jurnal Ilmiah Teunuleh, 2024)
The ability and skills of teachers in classroom management significantly influence the effectiveness of the teaching and learning process. A teacher can create a positive and enjoyable learning environment for students. Classroom management is the task performed by the teacher responsible for teaching activities to ensure that everything runs smoothly and effectively. In carrying out their roles as educators, mentors, leaders, and trainers of students, a teacher must understand and be aware of various aspects of behavior, particularly their students' behavior. Elementary school students have characteristics such as a love for play, a tendency to be active, a preference for working in groups, and a desire to experience, do, and demonstrate things directly. However, many teachers still do not fully understand the meaning of these characteristics. Therefore, further understanding is needed to deepen teachers' insights into classroom management skills that align with the characteristics of elementary school students. This study uses a literature review approach, with data collection based on findings from various journal sources and books related to the topic. The study concludes that the skills teachers must possess to manage classrooms in elementary schools include: 1) Understanding Child Development; 2) Effective Communication Skills; 3) Time Management; and 4) Understanding Individual Needs.